Towards a Critically Conscious Approach to Social and Emotional Learning in Urban Alternative Education: School Staff Members’ Perspectives - Christopher D. Slaten; Decoteau J. Irby; Kevin Tate; Roberto Rivera (Journal for Social Action in Counseling and Psychology)
Social and emotional learning (SEL) has been well researched and validated as an important component of youth education (Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, 2011; Elias et. al., 1997). However, much of the literature implies a very monolithic approach to SEL interventions (Watts, Griffith, & Abdul-Adil, 1999). The current study examines a predominately African-American urban alternative school’s unique approach to reaching students’ SEL needs. Utilizing Consensual Qualitative Research (Hill, 2012), researchers interviewed 15 staff members at the school, ranging from teachers to mental health professionals to community educators, to obtain a thorough understanding of the unique approaches to SEL within urban alternative education. Implications for educators and mental health professionals working in alternative educational settings are discussed